PERBANDINGAN PEMBELAJARAN MODEL COOPERATIFE LEARNING TIPE JIGSAW I DENGAN TIPE JIGSAW II TERHADAP HASIL BELAJAR SISWA PADA KONSEP SISTEM PENCERNAAN PADA MANUSIA DI KELAS VIII SMP NEGERI 1 CIAWIGEBANG - Pipin Pinuhatul; Anna Fitri Hindriana; Haruji Satianugraha (Quagga : Jurnal Pendidikan dan Biologi, 2016)
This research is conducted to find out whether or not the differences in the result of student learning that significant through the use of cooperative learning Type I and II jigsaw. The experiment is conducted at SMP Negeri 1 Ciawigebang in September 2012 in the second half of the school year 2012/2013 on the concept of Human Digestive System. The population in this research is the students at the Eighth Grade of SMP Negeri 1 Ciawigebang which consist all of nine classes. They are class VIII A till class VIII I with 351 students.                                                                 The normality test of jigsaw I and II classes obtain X2 count B-21, 79 and -20, 88 , while X2table is 7,81 and shows this data are normal distribution. For test homogeneity of variance both the data are normal distribution. For test homogeneity of variance both the data and the calculate values Fcount is 1,15 while Ftable is 1,74 if Fcount is lower than Ftable (1,15 1,74) so the variance of the two data are homogeneous. From the percentage calculation of the students reaction that agree with using Cooperative Learning Models Jigsaw I is 62,34% and jigsaw II is 59,46%. The hypothesis test is use Ttest and the calculate values Fcount is 0,87 and Ttable is ± 1,99. If Tcount on the interval Ttable, so is accepted, it means that there is no difference between jigsaw I and II class. But based on percentage student who pass or fill the KKM (73) the student jigsaw I class only produce percentage about 43%, while jigsaw II class produce percentage about 49%. So based on the student who pass the KKM jigsaw I and jigsaw II class has difference experience. The result from this research is Cooperative Learning Models jigsaw I and II has difference that not too big in the achieve of result study especially in the research that the writer do at the concept of Human Digestive System.Key Words : Learning Model jigsaw I, Learning Model jigsaw II. The result study of student, Human Digestive System.